PENGARUH PENGGUNAAN METODE RESITASI TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VII SEMESTER GENAP SMP NEGERI 1 TRIMURJO - Sinta Alfiana Sari; Tiara Anggia Dewi (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
Based on the analysis of research data using a simple linear regression formula obtained t-count = 3.78 suppose t-table = 1.70 at a significance level of 0.05 or at 5% and t-table = 2.46 at the level of significance of 0, 01 or 1% thus t-count> t-table. This means that simple linear regression is real, or the hypothesis is accepted, and from the results of the study it can be concluded that: The use of recitation methods can improve the Integrated Social Studies learning outcomes of VII.1 class even semester of SMP Negeri 1 Trimurjo on the subject of Scarcity and Human Needs. It is proven by the average pre-test measurement before the learning process is 9.37 and the average post-test value after being given treatment uses variable X of 77.94. Students who were declared complete with KKM ≥ 71 after being given treatment as many as 24 students or as much as 75% and students who were declared as incomplete as many as 8 students or 25%, thus the learning process was said to be successful. Keywords: Learning Outcomes, Resitasi Method